Handedness and religiosity, a two-nation study: Evidence that hemispheric functioning may influence religious beliefs - Ellis, Lee; Das, Shyamal; Hoskin, Anthony W. (Utan Kayu Publishing, 2023)
Prior research has reported that so-called consistent-handers are more religious than non-consistent-handers. This study analyzed data bearing on this possibility using large samples of college students from two different countries; Malaysia and the United States. When samples from both countries were separated by sex, no significant support for this prior research was found. However, when we analyzed our data with handedness dichotomized between right-handers and non-right-handers, some significant relationships were found. Among females in both countries, left- and mixed-handers expressed lower degrees of certainty about the existence of God and life-after-death. Also, right-handedness and religious service attendance were positively and significantly associated among Malaysian males. Among US males, however, belief in God was actually significantly stronger among right-handers than among left and mixed-handers. Assuming that right handedness is a rough proxy for left hemispheric dominance, our findings provide some support for the hypothesis that right hemispheric dominance is associated with orthodox religiosity at least among females.